High‐Shear‐Strength Waterborne Polyurethane/Acrylic Soft Adhesives. Issue 6 (28th August 2012) - Degrandi‐Contraires, Elise; Lopez, Aitziber; Reyes, Yuri; Asua, José M.; Creton, Costantino
Abstract Urethane/acrylic hybrid latex particles are prepared by miniemulsion polymerization for an application as soft adhesives. The polymerization of the acrylic monomers and grafting of an isocyanate functionalized PU on a hydroxyl functionalized monomer (HEMA) take place simultaneously, resulting in a complex PU/acrylic network while avoiding any macroscopic phase separation. Its structure can be tuned by changing the extent of grafting and a specific model is applied to analyze the final polymer microstructure. The resulting materials have a low level of adhesion but display an exceptionally high resistance to shear. Two parameters are varied: the fraction of HEMA in the monomer composition and the diol concentration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>